Social determinants of college completion and wealth mobility: a life course approach to educational completion among young baby boomers - Aronson, Matt, author; Lacy, Michael, advisor; Cross, Jennifer, committee member; Stretesky, Paul, committee member; Most, David, committee member (Colorado State University. Libraries, 2015)
This dissertation fits within both the sociology of education subfield and the mainstream discipline's longstanding concern over stratification, which is generally understood as the systematic persistence of unequal social statuses and socioeconomic positions in society. Educational status, especially the condition of having completed a four-year undergraduate degree, represents a key feature of socioeconomic position and an important predictor of various life chances in the United States. One limitation of previous sociological research on education is that most studies have asked about the whether of educational attainment without giving much attention to the when of degree completion. A main goal of this dissertation, then, is to remedy that inattention by asking how family-level and individual-level conditions during people's childhoods may influence the timing of their four-year college completions. Another goal is to examine wealth mobility, and to ask whether timely college completion influences wealth mobility from early- to mid-adulthood. I offer three essays, each of which addresses these goals in different ways. The first study compares results from an event history model of high school completion and argues for treating educational completion as an event in time rather than as a binary or categorical outcome. That section offers a methodological contribution to current scholarship as sociologists of education are increasingly taking advantage of longitudinal data sets. The next essay asks how some characteristics and conditions early in individuals' lives may influence the timing of their college completions. I consider teenage childbearing, family poverty, maternal education and other factors in an attempt to provide an alternative to the conventional understanding of race-ethnicity as a predictor of individuals' conditional odds of college completion. The fourth essay departs from the emphasis on "timing of college completion" as an outcome and instead focuses on several under-examined questions about wealth mobility (movement within the wealth distribution over the life course) and whether timely college completion and adolescent employment are associated with upward wealth mobility over the adult life course. The final section also makes a basic contribution to social scientists’ understanding of wealth dynamics among the National Longitudinal Survey of Youth's late baby boomer cohorts.